PENGARUH KEPERCAYAAN DAN KOMITMEN TERHADAP RANTAI PASOKAN YANG DIMEDIASI OLEH KETERHUBUNGAN PEMASOK PADA PEMILIK TOKO KELONTONG DI DKI JAKARTA - Andreas Wijaya (Universitas Bunda Mulia, 2017)
This study aims to determine the effect of trust and commitment in the relationship between the suppliers and the owner of a grocery store in Jakarta. The data was collected through questionnaires and processed using IBM AMOS 24The data has been collected through questionnaires and processed using IBM AMOS 24 and it can be concluded that trust has an influence on the commitment and supplier relationship, and supplier relationships have an influence on the supply chain, but commitments have no effect on supplier relationshipsKeywords: Trust, Commitment, Supplier Relationships, Supply Chain